2014
DOI: 10.22146/majkedgiind.8758
|View full text |Cite
|
Sign up to set email alerts
|

Perawatan Maloklusi Angle Klas I dengan Gigi Depan Crowding Berat dan Cross Bite Menggunakan Teknik Begg pada Pasien dengan Kebersihan Mulut Buruk

Abstract: Gigi depan crowding/berjejal parah dan cross bite adalah kasus yang sering dijumpai pada perawatan ortodontik. Gigi crowding dapat menyulitkan membersihkan mulut pada area gigi crowding sehingga dapat menyebabkan masalah periodontal. Salah satu keuntungan perawatan ortodontik cekat dengan teknik Begg adalah menghasilkan gaya yang ringan dalam megkoreksi gigi berjejal dan cross bite dapat memberikan kenyamanan pada pasien. Tujuan perawatan ini adalah untuk mengkoreksi gigi berjejal dan cross bite dalam waktu ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
0
5
0
3
Order By: Relevance
“…It was also found that there was a close relationship between the amount of tooth material and the width of the apical base, thus creating a formula for measuring Howe's Index. [5][6][7]13 In this study, we found that the average value of total tooth material, the arch length, the average basal arch width, and the average ratio of Howe's Index were all higher in male students compared to female students. This study had the same results as the study conducted by Pawar and Jayade in Karnataka Utara.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It was also found that there was a close relationship between the amount of tooth material and the width of the apical base, thus creating a formula for measuring Howe's Index. [5][6][7]13 In this study, we found that the average value of total tooth material, the arch length, the average basal arch width, and the average ratio of Howe's Index were all higher in male students compared to female students. This study had the same results as the study conducted by Pawar and Jayade in Karnataka Utara.…”
Section: Discussionmentioning
confidence: 89%
“…Cast analysis serves as a guide and has been the gold standard to determine proper diagnosis and treatment planning in orthodontic treatment for many years. [5][6][7]12 Various methods have been used for measuring and analysing the study models, including calipers, rulers, and other measuring tools. The data obtained from the measurement results were calculated with the relevant formulas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overcrowded teeth are more at risk of suffering from periodontitis than the loose teeth [20]. This is probably occurred because the respondents who have loose or crowded teeth have a lower chance of cleaning the entire tooth surface, when compared to respondents who have loose teeth [21].…”
Section: Tooth Condition According To the Early Detection Of Periodonmentioning
confidence: 99%
“…April 2017; 3(1): 35 -42 ISSN 2460-0164 (print) ISSN 2442-2576 (online) men du kung pekerjaan tenaga kesehatan gigi guna mengetahui keadaan sebelum dan sesudah perawatan. 2 Layanan radiologi membutuhkan sumber daya manusia sebagai petugas radiografer untuk melaksanakan pelayanan. Petugas radiografer dituntut untuk memiliki pengetahuan dasar tentang komponen-komponen yang bekerja menghasilkan radiasi ionisasi pada pemaparan sinar X, bertanggung jawab terhadap dosis radiasi yang diterima oleh pasien, serta memiliki pengetahuan dan keterampilan untuk dapat menghasilkan radiograf yang berkualitas dan meningkatkan kepuasan pasien.…”
Section: Pendahuluanunclassified